The survey of hypertension and its risk factors among industrial male workers - Hadi Daneshmandi; Alireza Choobineh; Abdolreza Rajaee Fard; Mina Babashahi (Gonabad University of Medical Sciences, 2018)
Hypertension is nowadays increasingly observed among the workforce population. There are many risk factors for hypertension. This study was conducted to survey hypertension and its associated risk factors among male workers of the industrial sector in Shiraz city. 500 male workers employed in Shiraz city industries participated voluntarily (age range of 20 to 59 years). A questionnaire and direct measurements were used to collect required data. The questionnaire consisted of two parts including a) demographic and occupational and b) anthropometric (height, weight, BMI, WHtR) and physiological (blood pressure and VO2-max) characteristics of the subjects. Mean (standard deviation) of systolic and diastolic Blood Pressure (BP), and Mean Arterial Pressure (MAP) in workers were 128.37±14.78, 83.13±13.10, and 98.21±13.36 mmHg, respectively. The results showed that systolic and diastolic BP, and MAP significantly were related to BMI, shift work, and smoking. Also, statistical analysis revealed that mean values of VO2-max between workers with normal and high blood pressure are significantly different. The results of this study demonstrated that domestic and occupational life style and cardio-respiratory fitness are the risk factors for hypertension in the studied workers.